2016
DOI: 10.1186/s12986-016-0136-4
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring for compliance with a ketogenic diet: what is the best time of day to test for urinary ketosis?

Abstract: BackgroundThe ketogenic diet (KD) is a very low-carbohydrate, high-fat and adequate-protein diet with no calorie limit that induces a metabolic condition called “physiological ketosis”. It was first introduced to treat epilepsy in the 1920s and has become quite popular recently as weight-loss and performance-enhancing diet. Its therapeutic use in a range of diseases is under investigation. During KD interventions people are supposed to monitor compliance with the dietary regimen by daily urine testing for keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…Moreover, participants were instructed to accurately fill out 3-day (two weekdays and one weekend day) dietary recording forms for 4 weeks and reported to the laboratory every week with the dietary recording forms to evaluate diet compliance and get follow-up dietary suggestions. To further ensure their compliance with LC, we also provided the participants with reagent strips (UROPAPER, Suzhou First Pharmaceutical Co. Ltd., Suzhou, China) to assess urinary ketones by themselves every day in the morning or after dinner [42]. Food records were analyzed for energy intake and macronutrient contents by the same dietician using the nutrition analysis and management software (NRISM, version 3.1, China).…”
Section: Diet Interventionmentioning
confidence: 99%
“…Moreover, participants were instructed to accurately fill out 3-day (two weekdays and one weekend day) dietary recording forms for 4 weeks and reported to the laboratory every week with the dietary recording forms to evaluate diet compliance and get follow-up dietary suggestions. To further ensure their compliance with LC, we also provided the participants with reagent strips (UROPAPER, Suzhou First Pharmaceutical Co. Ltd., Suzhou, China) to assess urinary ketones by themselves every day in the morning or after dinner [42]. Food records were analyzed for energy intake and macronutrient contents by the same dietician using the nutrition analysis and management software (NRISM, version 3.1, China).…”
Section: Diet Interventionmentioning
confidence: 99%
“…To ensure compliance with LC, all subjects took urinary ketone assessments daily and kept 3 day food records (2 weekdays and 1 weekend day). Subjects received self-testing reagent strips (UROPAPER, Suzhou First Pharmaceutical Co. Ltd., Suzhou, China) to measure their urinary ketones daily in the early morning or after dinner [26], and the results were recorded in the offered logbook. In addition, subjects were instructed to keep 3 day food records, 2 weeks before intervention and 4 weeks during intervention.…”
Section: Diet Interventionmentioning
confidence: 99%
“…The seemingly discrepancy to the finding of unchanged mean energy intake is discussed in more detail in the main study [6]. The main study showed that a non-energy-restricted KD leads to a significant but mild weight loss over the entire 6-week KD period, although mean energy intake did not change [6,36]. Even if the diet was supposedly not energy restricted, no measurements of energy expenditure or strict dietary compliance was documented and a slight reduction in energy intake could be possible.…”
Section: Discussionmentioning
confidence: 89%